Pasture larval burden – an indirect method to count strongyle helminth larvae in grazing land of sheep - M.K. Vijayasarathi; C. Sreekumar; R. Venkataramanan; M. Raman (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An approximate amount of 250 g of fresh pasture samples were collected in the “W” shaped sampling method from five beneficiary villages of Network Project on Sheep Improvement (NWPSI) in and around of Kancheepurm District of Tamil Nadu at weekly interval before sunrise during winter and summer months. The samples were processed by Modified Baermann’s apparatus technique. The results revealed that non-parasitic soil larvae alone during the months of December 2013 to March 2014. It might be due to unfavourable environmental conditions like dearth of rainfall and high temperature during the period of pasture sample collection. Hence, it was inferred that ideal environmental condition was needed for development of strongly larval stage.